Assessment Of Sanitation And Hygiene Practices In Bubare Sub-County Rubanda District In Southwestern Uganda. - Arinayesu, Brilliant Cyria (Kabale University, 2024)
The study was the assessment of sanitation and hygiene practices in the Bubare sub-county, Rubanda District in southwestern Uganda following the study objectives which were; to establish the different forms of sanitation and hygiene practices used in the study area and to examine people’s awareness of the consequences of poor sanitation and hygiene practices in the study area. The study employed a community-based cross-sectional survey design. Data collection was done using qualitative and quantitative methods across a sample of 96 respondents. Questionnaires were also used to gather data from respondents. The findings of the study revealed that female respondents were more highly represented in the study than their male counterparts. Findings of the study also found that there were different forms of sanitation and hygiene including hand washing, personal hygiene, safe water and drinking water hygiene, waste management, environmental hygiene, and latrine coverage. The findings of the study revealed that most households had latrines and hand washing facilities in the Bubare sub-county Rubanda district. The study concluded a notable lack of access to basic sanitation facilities in the Bubare sub-county. Many households do not have access to improved sanitation facilities such as ventilated latrines, leading to open defecation and increased risk of diseases. Hygiene practices in the area are substandard, with inadequate hand washing facilities and poor hygiene behaviors observed. This contributes to the spread of diseases such as diarrhea and cholera. The study recommended that there is a need for increased awareness and education on the importance of sanitation and hygiene practices. Many community members may not be aware of the link between poor sanitation and disease transmission.